2018
DOI: 10.1029/2018gc007723
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Vortex States in Small Octahedral Particles of Intermediate Titanomagnetite

Abstract: Fine particles of titanomagnetites (Fe3‐xTixO4, x > 0.5) in the pseudo‐single‐domain (PSD) size (0.5–20 μm) are important carriers of natural remanent magnetization in basalts. Understanding the mechanism of magnetic recording in these grains has important implications for paleomagnetic studies. This study reports first observations of magnetic vortex states in intermediate titanomagnetite. We imaged magnetic structures of 109 synthetic titanomagnetite grains with x = 0.54 (TM54) and 1–4‐μm size using magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 71 publications
4
18
0
Order By: Relevance
“…The titanomagnetite sample was synthesized using the glass‐ceramic method (Worm & Markert, ) and described in detail in Khakhalova et al (). The sample contains titanomagnetite grains dispersed in a nonmagnetic glassy silicate matrix.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The titanomagnetite sample was synthesized using the glass‐ceramic method (Worm & Markert, ) and described in detail in Khakhalova et al (). The sample contains titanomagnetite grains dispersed in a nonmagnetic glassy silicate matrix.…”
Section: Methodsmentioning
confidence: 99%
“…To gain further insights into TRM theory and provide observational data for validating micromagnetic models, we conducted high‐temperature domain observations of vortex states in two grains of intermediate titanomagnetite (Fe 3‐x Ti x O 4 with x = 0.54, or TM54), with known crystallographic orientations and diameters of ~1.5 μm. From a previous study on the same sample at room temperature (Khakhalova et al, ), it was found that these grains display SV states as the most common LEM state (global energy minimum or GEM state) and several multivortex (MV) states presumed to be higher‐energy LEM states. Here we use variable‐temperature magnetic force microscopy (MFM) to image vortex state evolution during in situ thermal demagnetization and TRM acquisition in a weak magnetic field of ~0.1 mT.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…At larger sizes these grains form either (1) PSD magnetization structures with inhomogeneous structures and no clear domains or (2) MD magnetization structures, with distinct uniformly magnetized regions with domain walls. Previous studies using micromagnetic calculations commonly model geometries of idealized shapes (Fabian et al, 1996;Fukuma & Dunlop, 2006;Khakhalova et al, 2018;Newell & Merrill, 1999;Yu & Tauxe, 2008;Witt et al, 2005, Williams & Dunlop, 1995. Natural iron oxide geometries are usually more complicated (e.g., Larson et al, 1969;Shaar & Feinberg, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To acquire 3-D morphologies of such true particle geometries, we used nanotomography by Focused Ion Beam Scanning Electron Microscopy (FIB-SEM). Examples of other studies using MERRILL on magnetic oxides include submicron grains of iron (Einsle et al, 2016;Nagy, Williams, Tauxe, & Muxworthy, 2019a;Nagy, Williams, Tauxe, Muxworthy, & Ferreira, 2019b;Nichols et al, 2019;Shah et al, 2018); magnetite (Lascu et al, 2018) and titanomagnetite (Khakhalova et al, 2018;Khakhalova & Moskowitz, 2019).…”
Section: Introductionmentioning
confidence: 99%